2021
DOI: 10.1038/s41420-021-00543-8
|View full text |Cite
|
Sign up to set email alerts
|

Probing tissue transglutaminase mediated vascular smooth muscle cell aging using a novel transamidation-deficient Tgm2-C277S mouse model

Abstract: Tissue transglutaminase (TG2), a multifunctional protein of the transglutaminase family, has putative transamidation-independent functions in aging-associated vascular stiffening and dysfunction. Developing preclinical models will be critical to fully understand the physiologic relevance of TG2’s transamidation-independent activity and to identify the specific function of TG2 for therapeutic targeting. Therefore, in this study, we harnessed CRISPR-Cas9 gene editing technology to introduce a mutation at cystein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Mice exposed to neonatal hypoxia had higher PWV and passive modulus at P60 with a further increase by P120, without a change in blood pressure, when compared to normoxic controls. The elevated stiffness without BP changes in the neonatal hypoxia group were similar to those observed in middle-aged mice during aging (Steppan et al, 2019;Wang, Chen, et al, 2021), supporting the hypothesis that exposure to hypoxia during the neonatal period accelerates arterial aging. This is of particular interest, as prior clinical studies have clearly shown that arterial stiffening in childhood and adolescence due to obesity, diabetes, and congenital heart disease is predictive of early onset CVD in adulthood (Dangardt et al, 2013;Hacker et al, 2018;Madsen et al, 2021;Urbina et al, 2010).…”
Section: Discussionsupporting
confidence: 79%
“…Mice exposed to neonatal hypoxia had higher PWV and passive modulus at P60 with a further increase by P120, without a change in blood pressure, when compared to normoxic controls. The elevated stiffness without BP changes in the neonatal hypoxia group were similar to those observed in middle-aged mice during aging (Steppan et al, 2019;Wang, Chen, et al, 2021), supporting the hypothesis that exposure to hypoxia during the neonatal period accelerates arterial aging. This is of particular interest, as prior clinical studies have clearly shown that arterial stiffening in childhood and adolescence due to obesity, diabetes, and congenital heart disease is predictive of early onset CVD in adulthood (Dangardt et al, 2013;Hacker et al, 2018;Madsen et al, 2021;Urbina et al, 2010).…”
Section: Discussionsupporting
confidence: 79%
“…These observations fuel maturing evidence of augmented calcium signaling 68 and contractility 69,70 in SMCs embedded within a stiff matrix. Note, Retailleau et al reported that Piezo-1 signaling promotes thickening of the murine caudal artery by stimulating the Ca 2+ -dependent catalytic activity of transglutaminases 71 and tissue transglutaminase contributes to vascular stiffening during aging [72][73][74] . Therefore, modulation of the actin cytoskeletal architecture in vSMC (Figure 7A) may heighten contractility (Figure 7B-C) and contribute to ECM stiffening (Figure 6B-C; Table S3) by mediating expression and activation of mechanosensitive Piezo-1 in the ATA media during aging (Figure 7A).…”
Section: Discussionmentioning
confidence: 99%
“…Other possibilities rely on comparisons with vertebrate animals. For example, transglutaminase causes age-associated vascular stiffening and dysfunction in mice, resulting in a loss of vascular compliance as this mammal ages [ 59 ]. It is possible that silencing mosquito TGase3 reduces heart stiffening, thereby increasing cardiac efficiency and reducing the heart rate in uninfected mosquitoes.…”
Section: Discussionmentioning
confidence: 99%